Unhinging the machinery of sepsis: An unexpected role for vascular smooth muscle. Issue 4 (22nd August 2018) - Englert, Joshua A.; Christman, John W.; Ballinger, Megan N.
Abstract : Discussion on the important role of cellular interaction in the design of potential sepsis therapeutics.